1869 Wash. Sess. Laws 203, An Act Relative to Crimes and Punishments And Proceedings In Criminal Cases, ch. 2, § 31. - (:unkn) unknown (My University, 1869)
Every person who shall assault and beat another with a cowhide or whip, having with him at the time a pistol or other deadly weapon, shall, on conviction thereof, be imprisoned in the county jail not more than one year nor less than three months, and be fined in any sum not exceeding one thousand dollars.
Keywords: COMMITTING CRIME W/ WEAPON